Products, Prices, Locations, and Advertisements on Purchase Decisions for Apartment Customers in Sidoarjo: Produk, Harga, Lokasi, dan Iklan Terhadap Keputusan Pembelian pada Pelanggan Apartment di Sidoarjo - Islamia, Nanda Putri; Indayani, Lilik (Universitas Muhammadiyah Sidoarjo, 2023)
This research is a descriptive correlative quantitative research, where this research was conducted to test how much influence the product, price, location and advertising have on purchasing decisions at Tamansari Prospero Apartments Sidoarjo. This research was conducted on 86 consumers who became respondents at the Tamansari Prospero Apartment in Sidoarjo. Based on the results of the simultaneous F test, it can be said that 5. Product, price, location, and advertisement simultaneously influence consumer purchasing decisions at the Tamansari Prospero Apartment.